Spontaneous Pneumomediastinum in a Teenager After Physical Exercise: a Benign and Rare, but Sometimes Challenging, Entity - Spiliopoulos, Kyriakos (Med Arch, 2020)
INTRODUCTION: Pneumomediastinum defines a condition in which free air is present in the mediastinum usually caused by alveolar rupture resulting from a sudden increase in the intrathoracic pressure and air tracking along the tracheobronchial tree. CASE REPORT: We present a case of a 16-year-old male patient referred to our department due to persisting odynophagia, and retrosternal chest pain. A performed chest-CT revealed presence of free air in the mediastinum, without evidence of pneumothorax, or subcutaneous emphysema. Under the diagnosis of spontaneous pneumomediastinum (SPM) the treatment included conservative therapy with analgesics, rest, and oxygen. CONCLUSION: SPM is a rare benign condition with nonspecific presenting clinical signs; thus its diagnosis remains mostly one of exclusion. Thorough history-taking, beside radiographic studies, may be the key to confirm the diagnosis.